Evaluation of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Bioceramic Ceremagnum plus against E. faecalis, Staphylococcus aureus and Streptococcus mutans with MTA Type of manuscript: In vitro study - Mitra, Anusua; Karobari, Mohamed Isaqali (Journal of Neonatal Surgery, 2025)
Background: Microbial persistence is a major cause of pulpal and periapical treatment failure. Enterococcus faecalis, Streptococcus mutans, and Staphylococcus aureus are among the most frequently implicated pathogens in secondary and persistent endodontic infections. An ideal pulp capping or root repair material should combine bioactivity with strong antimicrobial properties. Aim: To evaluate and compare the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Ceremagnum Plus, a novel bioceramic material, with mineral trioxide aggregate (MTA) against E. faecalis, S. mutans, and S. aureus. Materials and Methods: Ceremagnum Plus was indigenously synthesized and compared with MTA Angelus. Standardized eluates were prepared and tested against ATCC strains of the three microorganisms. MIC was determined using the broth microdilution method, and MBC was confirmed by subculturing MIC-negative wells onto Brain Heart Infusion agar. Data were statistically analyzed using one-way ANOVA and Tukey’s post hoc test with significance set at p < 0.05. Results: All materials demonstrated measurable antimicrobial activity. Ceremagnum Plus exhibited the largest inhibition zones against S. aureus and S. mutans and was comparable to calcium hydroxide against E. faecalis. MIC values for Ceremagnum Plus were ≤ 25 mg/mL for all organisms, lower than MTA for S. mutans and S. aureus. MBC values were 50 mg/mL for all groups, confirming bactericidal potential. Conclusion: Ceremagnum Plus shows strong antibacterial activity, superior to MTA against S. aureus and S. mutans, with comparable efficacy against E. faecalis. Its ability to achieve bactericidal action at clinically relevant concentrations supports its potential role as an effective pulp capping and root repair material.